(untitled) (Research, Society and Development, 2022)
Tangerines represent the second largest group of citrus fruits produced worldwide. In Brazil, its production is concentrated in the Southeast and South regions of the country. The most cultivated variety in Brazilian orchards is the ’Ponkan’ mandarin, which is highly appreciated for fresh consumption. In recent years there have been changes in the profile of consumers and an increase in the search for residue-free food. New alternative conservation methods, such as the use of coatings and physical treatments in fruit storage, have been studied. The objective of this work was to evaluate the use of cassava starch and gelatin coatings, combined with the application of UV-C radiation, to prolong the shelf life of ’Ponkan’ tangerines during storage. The experiment was completely randomized, containing as treatment factors: 3% cassava starch and gelatin coatings, UV-C application (with and without) and storage days (5, 10 and 15). The results showed that there was an increase in the pH of fruits treated with cassava starch and gelatin, with application of UV-C. The loss of fruit mass increased with the storage period and for SST there were no differences between treatments. The color attributes indicate that the cassava starch was efficient in maintaining the fruit color during storage. It was concluded that the use of 3% cassava starch and gelatin coatings were not efficient in maintaining the chemical quality attributes of ’Ponkan’ mandarin fruits and the application of UV-C radiation had no effect on the parameters analyzed.